PROGRAM MERDEKA BELAJAR KAMPUS MERDEKA MEMBANGUN DESA/KULIAH KERJA NYATA TEMATIK PEMBINAAN KESENIAN GENDER WAYANG DI DESA ADAT KUKUB - Weda Wikantika, I Putu; Kodi, I Ketut; Adhi Santika, Sang Nyoman Gede (Pusat Penerbitan LP2MPP ISI Bali, 2025)
The rapid development of times demands students to possess skills and knowledge relevant to the issues faced by society. In this context, the